2018
DOI: 10.1002/ajmg.a.40523
|View full text |Cite
|
Sign up to set email alerts
|

Novel de novo pathogenic variant in the ODC1 gene in a girl with developmental delay, alopecia, and dysmorphic features

Abstract: The ornithine decarboxylase 1 (ODC1) gene plays an important role in physiological and cell developmental processes including embryogenesis, organogenesis, and neoplastic cell growth. Here, we report an 32‐month‐old Caucasian female with a heterozygous de novo nonsense mutation in the ODC1 gene that leads to a premature abrogation of 14‐aa residues at the ODC protein c‐terminus. This is the first human case confirming similar symptoms observed in a transgenic ODC1 mouse model first described over 20 years ago.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 22 publications
(42 reference statements)
2
50
0
Order By: Relevance
“…The first rate‐limiting step in the de novo synthesis of polyamines involves the conversion of ornithine to putrescine via ornithine decarboxylase (ODC), encoded by ODC1 (see Figure ). In the December 2019 issue of the American Journal of Medical Genetics part A, Bupp, Schultz, Uhl, Rajasekaran, and Bachmann () report the first patient with ODC superactivity. Subsequently, Rodan et al () described four additional patients with…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first rate‐limiting step in the de novo synthesis of polyamines involves the conversion of ornithine to putrescine via ornithine decarboxylase (ODC), encoded by ODC1 (see Figure ). In the December 2019 issue of the American Journal of Medical Genetics part A, Bupp, Schultz, Uhl, Rajasekaran, and Bachmann () report the first patient with ODC superactivity. Subsequently, Rodan et al () described four additional patients with…”
mentioning
confidence: 99%
“…Bupp et al () described elevation of putrescine in red blood cells, while Rodan et al () reported elevation of N‐acetylputrescine in plasma from one patient. The latter is reminiscent of what has been reported in Snyder‐Robinson syndrome, where the accumulated substrate undergoes N‐acetylation, and the elevated N‐acetylated product (N8‐acetylspermidine) can be identified via plasma metabolomics (Abela et al, ).…”
mentioning
confidence: 99%
“…All of the patients in our series have very closely located truncating variants in the final exon of the ODC1 gene, proximal to the C‐terminal 37‐amino acid destabilization region of the protein. As such, these variants are predicted to lead to a mutant protein that both escapes nonsense‐mediated decay (NMD) and has reduced degradation compared to wild‐type, resulting in a net gain‐of‐function of ODC1 enzyme activity, as has been recently demonstrated (Bupp et al, ). In addition, the very close proximity of the reported variants suggests that this region may be a hotspot for DNA rearrangement.…”
Section: Discussionmentioning
confidence: 94%
“…For its degradation, the ODC1 monomer noncovalently binds with an ODC antizyme protein, inactivating it and directing it for ubiquitin‐independent degradation by the proteasome. The ODC antizyme binds to a C‐terminal 37‐amino acid destabilization region of the protein (Bupp et al, ; Moinard et al, ; Nowotarski, Woster, & Casero, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation